Evaluating the perception of structural defects during implementation of RC T-beams - Elsaid Bayoumi (University Of Muhammadiyah Jakarta, 2022)
Most defects during construction projects are due to human errors which happen due to poor workmanship. This study involved 8 simply supported RC T-beams subjected to uniformly distributed load at both-edges of slab. The investigated parameters were the effect of malposition of slab reinforcement, unequal configuration of slab reinforcement and change in bar diameter of slab reinforcement. The experimental results showed that; malposition of slab reinforcement leads to a lower load carrying capacity of the slab and consequently flexural resistance decreased and slab deflection increased. The irregularity of the reinforcing bars in concrete slab affected the load carrying capacity of T-beam. Well-arranged distribution of reinforcement improves the ductile behavior of slab and reduced value of deflections at failure. Using reinforcing steel bars with diameters higher than 8mm in the reinforcement helped the slab to withstand more loads. The use of 10mm diameter in reinforcement of the slab enhances the serviceability of T-beams.